FIQH INDONESIA; ANTARA PEMBAHARUAN DAN LIBERALISME HUKUM ‎ISLAM - Syamsul Falah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2017)
Fiqh is the discipline that is most affected by the changes in human life that come incessantly. Fiqh is intended to harmonize between the syar'i texts that have completed their revelations and are standardized in the Qur'an and assunaah with humans as objects of jurisprudence that never stop changing. So fiqh is the most extensive space for new ijitihad-ijitihad. Islamic jurisprudence and law will always adjust to socio-cultural conditions, and socio-historical and space that surrounds it, as well as in Indonesia, fiqh is used as a means in determining the direction of religious life of the Islamic community in Indonesia, the basic attitude of this Islamic tradition seems to have become the dominant choice and grip among fiqh experts in Indonesia. The dynamics of Indonesian jurisprudence in the Syafiiyah discourse, this can be understood because the process of Islamization in Indonesia since the 12th and 13th centuries was a time when the development of Islamic law was in a time of crisis by closing the door of ijtihad as its lowest point even in the next period many figures who sued this matter, the experts did not dare to think as freely and creatively as possible so as to bring up a product that is timeless, space and time. Departing from the conceptul, the steps taken for Indonesian fiqh are: First, critical dialectics among Islamic law (particular texts containing practical rules), illat (causal law of wisdom) legal significance) Annadhoriyyah al ammah (azaz -azaz law) maqosidu syariah (the basic purpose of sharia) this analysis is one step that is normative deductive. Second, what is needed in analyzing these legal issues is an empirical-inductive step, which is analyzing problems related to reality, views, and practices in the community, in this case Urf Indonesia, through actual inductive field research. Having raised the offer of methodologies that are deductive and empirical-inductive normative and then make jurisprudence in Indonesia as living a living tradition that seems to be a breakthrough that makes Islamic law more lively so that sociologically and politically it will be easily proposed as legislation in Indonesia.